Knowledge and practices regarding Aedes control amongst residents of dengue hotspot areas in Selangor: a cross-sectional study - Zul-'Izzat Ikhwan Zaini,; Hidayatulfathi Othman,; Norhafizah Karim,; Nor Azimah Abd Rashid,; Mohamad Badrul Hisham Abas,; Mazrura Sahani,; Rozita Hod,; Saiful Azlan Nordin, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Dengue fever is endemic and remains a public health concern in Malaysia. The highest number of dengue cases occurred in Selangor in 2015. The majority of hotspot and outbreak areas in Malaysia were located in residential areas. Despite the high number of dengue prevalence in Malaysia, evidence for the level of community knowledge and practice of methods for Aedes control and prevention in the country remains scant. This cross-sectional study aimed to assess the demographic factors associated with the knowledge and practice of Aedes control and prevention methods. It also aimed to assess the associations and relationships between the public knowledge and practice of Aedes control and preventive activities involving Aedes larvae ovitraps (ALOTs), Mousticide, Denguard and other methods. Two residential areas that were considered as dengue hotspots were selected for the introduction of Aedes control and prevention programs. A sample size was calculated using G*power and a total of 152 residents who attended the dengue awareness events held at Section 3 and Section 8, Bandar Baru Bangi, Selangor, were recruited. A purposive sampling approach was adopted, and data were collected by using a pretested questionnaire with three subsections on sociodemographic information and on the knowledge and practice of Aedes control and prevention methods. No statistically significant (p>0.05) relationship between demographic factors and knowledge and practice scores was found. The results of χ2 square test showed a strong (φ-coefficient = 0.605) and significant (p<0.001) association between knowledge and practice scores. In addition, a strong and significant positive correlation (r=0.648, p<0.001) existed between knowledge and practice scores. In conclusion, health promotion programs that focus on educating the public regarding the use of Aedes larvae ovitraps (ALOTs), Mousticide, Denguard and other methods to prevent and control Aedes mosquitoes and that involve multiple stakeholders, such as government officials and responsible authorities, and the active participation of communities are crucial in the war against Aedes.